“An Unbendable Strength in Our Rosary”: Religious Life in the Gusen Concentration Camp - Lyon, Eileen Groth (Church history and religious culture, 2021)
Abstract The struggle to resist dehumanization and maintain a sense of identity and dignity in the German concentration camps has been a key theme in survivor testimonies. Some prisoners assert the paramount importance of religious faith in mustering the inner strength needed to survive. However, the clandestine nature of religious practice in the camps has meant that memoirs provide only fragmentary glimpses of these practices and their significance in the camps. This article seeks to reconstruct a fuller picture of the religious life of Catholic Poles at the Gusen Concentration Camp in Upper Austria from 1940 to 1945. In particular, the article focuses on the activities of a living rosary group organized by Wacław Milke and Władysław Gębik. This group was unusual in the breadth of its activities and its extensive network of contacts. Not only did it organize religious devotions, but it also provided life-saving practical assistance to other prisoners.